A Novel Developed Bioactive Composite Resin Containing Silver/Zinc Oxide (Ag/ZnO) Nanoparticles as an Antimicrobial Material against Streptococcus mutans, Lactobacillus, and Candida albicans. (16th October 2021) - Kachoei, Mojgan; Divband, Baharak; Rahbar, Mahdi; Esmaeilzadeh, Mahdiyeh; Ghanizadeh, Milad; Alam, Mostafa
Abstract : Aim . The objectives of this study were to develop a new bioactive composite resin containing silver/zinc oxide (Ag/ZnO) nanoparticles and investigate the effects on mechanical, cytotoxic, biocompatibility, and antimicrobial properties. Materials and Methods . Disc-shaped specimens were prepared from composite with and without nanoparticles in separate culture media containing Streptococcus mutans, Lactobacillus, and Candida albicans . Bracket bonding evaluation was performed on composite without nanoparticles (O), composite containing ZnO (Z) nanoparticles, composite containing ZnO nanoparticles and silver ions (A&Z), and composite containing Ag/ZnO nanoparticles (AZ) synthesized using optical precipitation. Results . Composite resin with nanoparticles (AZ, A&Z, and Z) showed significant antimicrobial properties (P  < 0.05). The mean shear bond strength of A&Z composite resin (13.61 ± 0.73 MPa) was significantly less than that of conventional composite resin (19.03 ± 4.12 MPa) (P  < 0.05). In addition, the mean shear bond strength of AZ composite resin (20.49 ± 1.03 MPa) was significantly higher than that of Z (16.35 ± 1.03 MPa) and A&Z composite resins. Conclusions . Incorporation of ZnO nanoparticles and their compounds into orthodontic composite resins induced antibacterial properties against oral pathogens, and of all these nanoparticles, the AZ group exhibited the best antimicrobial activity and highest shear bond strength.